Development of a reference and proficiency chemical list for human steatosis endpoints in vitro - Kubickova, Barbara; Jacobs, Miriam N. (Frontiers in Endocrinology, 2023)
The most prevalent liver disease in humans is non-alcoholic fatty liver disease, characterised by excessive hepatic fat accumulation, or steatosis. The western diet and a sedentary lifestyle are considered to be major influences, but chemical exposure may also play a role. Suspected environmental chemicals of concern include pesticides, plasticizers, metals, and perfluorinated compounds. Here we present a detailed literature analysis of chemicals that may (or may not) be implicated in lipid accumulation in the liver, to provide a basis for developing and optimizing human steatosis-relevant in vitro test methods. Independently collated and reviewed reference and proficiency chemicals are needed to assist in the test method development where an assay is intended to ultimately be taken forward for OECD Test Guideline development purposes. The selection criteria and considerations required for acceptance of proficiency chemical selection for OECD Test Guideline development. (i.e., structural diversity, range of activity including negatives, relevant chemical sectors, global restrictions etc.) is described herein. Of 160 chemicals initially screened for inclusion, 36 were prioritized for detailed review. Based on the selection criteria and a weight-of-evidence basis, 18 chemicals (9 steatosis inducers, 9 negatives), including some of the environmental chemicals of concern, were ranked as high priority chemicals to assist in vitro human steatosis test method optimisation and proficiency testing, and inform potential subsequent test method (pre-)validation.